2014
DOI: 10.1002/cphc.201402458
|View full text |Cite
|
Sign up to set email alerts
|

Modification of D–A–π–A Configuration toward a High‐Performance Triphenylamine‐Based Sensitizer for Dye‐Sensitized Solar Cells: A Theoretical Investigation

Abstract: In an attempt to shed light on how the addition of a benzothiadiazole (BTD) moiety influences the properties of dyes, a series of newly designed triphenylamine-based sensitizers incorporating a BTD unit as an additional electron-withdrawing group in a specific donor-acceptor-π-acceptor architecture has been investigated. We found that different positions of the BTD unit provided significantly different responses for light absorption. Among these, it was established that the further the BTD unit is away from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The TiO 2 lm were modelled with a stoichiometric anatase (101) surface as the (TiO 2 ) 38 cluster, which is similar to that described by Nazeeruddin et al 42 This model has been wildly used to study dye@TiO 2 adsorption and represents a reasonable choice between accuracy and computational convenience, and nicely reproduces the main electronic characteristics of TiO 2 nanoparticles. 8,[10][11][12][13][14][43][44][45] The HOMO, LUMO and HOMO-LUMO energy gap of the this cluster are calculated to be 27.98, 23.52, and 24.46 eV, respectively, while the lowest excitation is obtained as 3.75 eV (ref. 45) which is reasonably higher than typical band gaps of TiO 2 nanoparticles of a few nm size of 3.2-3.3 eV.…”
Section: Adsorption Of Organic Sensitizers On the Tio 2 Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…The TiO 2 lm were modelled with a stoichiometric anatase (101) surface as the (TiO 2 ) 38 cluster, which is similar to that described by Nazeeruddin et al 42 This model has been wildly used to study dye@TiO 2 adsorption and represents a reasonable choice between accuracy and computational convenience, and nicely reproduces the main electronic characteristics of TiO 2 nanoparticles. 8,[10][11][12][13][14][43][44][45] The HOMO, LUMO and HOMO-LUMO energy gap of the this cluster are calculated to be 27.98, 23.52, and 24.46 eV, respectively, while the lowest excitation is obtained as 3.75 eV (ref. 45) which is reasonably higher than typical band gaps of TiO 2 nanoparticles of a few nm size of 3.2-3.3 eV.…”
Section: Adsorption Of Organic Sensitizers On the Tio 2 Clustermentioning
confidence: 99%
“…There are mainly three kinds of dyes commonly used in DSCs, including ruthenium dyes, 4 porphyrin dyes [5][6][7][8][9] and metalfree organic dyes. [10][11][12][13][14][15] Compared with the other two dye types, the metal-free organic D-p-A dyes have received a great deal of attention due to their low cost, relatively simple synthetic procedure, ease of molecular modication and tailoring, high molar extinction coefficients, and environmental friendliness. [16][17][18] However, organic dyes also have their own drawbacks, such as a narrower absorption spectrum, and a faster charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…In recenty ears, density functional theory (DFT) has been widely used in the prediction of the optoelectronic properties of molecules. [25][26][27][28][29][30] Sanchez-de-Armas et al [26] investigated the electronic structures and optical properties of five coumarin-based dyes:C 343, NKX-2311, NKX-2586, NKX-2753 and NKX-2593 by using TDDFT methods. This investigation revealed that the positiona nd width of the first band in the electronic absorption spectra, the absorption threshold and LUMO energy with respectt ot he conduction band edge are keyp arameters to establish some criteria that allow evaluation of the efficiencyo fc oumarin derivatives as sensitizers in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complexity and cost of the synthetic process for dyes, theoretical calculations can provide a significant guide for experimental synthesis. In recent years, density functional theory (DFT) has been widely used in the prediction of the optoelectronic properties of molecules . Sanchez‐de‐Armas et al .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Recently,a ni mproved D-p-A construction,t he so-called D-A-p-A, in which an auxiliary heteroannulateda cceptor [13] is introducedi nto the molecular framework, has been systematically developed, which has led to excellent photovoltaic performance and photostability. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] To date, several D-A-p-Abased organics ensitizers have exhibited high powerc onversion efficiencies (PCEs) of over 10 %u nder full sun illumination (AM 1.5G, 100 mW cm À2 ), such as the indoline sensitizer YA422 (10.65 %), [31] the porphyrin sensitizer GY50 (12.75 %), [32] and the record one SM315 (13.0 %). [33] Compared to classical ruthenium sensitizers, such pure organic sensitizers are very promising candidates for future commerciala nd practical application, showingc omparably high PCEs and long-term stability.…”
Section: Introductionmentioning
confidence: 99%